Existence of solution for a generalized Schrödinger-Poisson system via bifurcation theory - Lima Alves Ricardo (Electronic journal of qualitative theory of differential equations, 2024)
In this paper, we study a generalized Schrödinger-Poisson system in a bounded domain of R3 and involving an asymptotically linear nonlinearity. We prove the existence of positive solutions using bifurcation theory.